Predictors of early mortality in multiple myeloma: Results from the Australian and New Zealand Myeloma and Related Diseases Registry (MRDR). (11th July 2022) - McQuilten, Zoe; Wellard, Cameron; Moore, Elizabeth; Augustson, Bradley; Bergin, Krystal; Blacklock, Hilary; Harrison, Simon; Ho, P. Joy; King, Tracy; Quach, Hang; Mollee, Peter; Rosengarten, Brian; et al.
Summary: The frequency and causes of early mortality in patients with newly diagnosed multiple myeloma (NDMM) have not been well described in the era of novel agents. We investigated early mortality in a prospective cohort study of all patients with NDMM registered on the Australian and New Zealand Myeloma and Related Diseases Registry (MRDR) at 36 institutions between July 2011 and March 2020. Early mortality was defined as death from any cause within the first 12 months after diagnosis. A total of 2377 patients with NDMM were included in the analysis, with a median (interquartile range) age of 67.4 (58.9–74.60 years, and 60% were male. Overall, 216 (9.1%) patients died within 12 months, with 119 (4.5%) having died within 6 months. Variables that were independent predictors of early mortality after adjustment in multivariable regression included age (odds ratio [OR] 1.07, 95% confidence interval [CI] 1.05–1.08; p  < 0.001), Eastern Cooperative Oncology Group performance status (OR 1.50, 95% CI 1.26–1.79; p  < 0.001), serum albumin (OR 0.95, 95% CI 0.93–0.98; p < 0.001), cardiac disease (OR 1.96, 95% CI 1.35–2.86; p  < 0.001) and International Staging System (OR 1.40, 95% CI 1.07–1.82; p  = 0.01). For those with a primary cause of death available, it was reported as disease‐related in 151 (78%), infection 13 (7%), other 29 (15%). Infection was listed as a contributing factor for death in 38% of patients.